Growth Performance and Hemato-Biochemical Profile in Broiler Chicken Supplemented on Shatavari (Asparagus racemosus) Root Powder and Vitamin E during Summer Season - Kant, Shashi; Ali, Nazim; Chandra, Gulab (Indian Journal of Animal Nutrition, 2018)
The effect of shatavari (Asparagus racemosus) and vitamin E supplementation on broiler performance, haematological and biochemical profile in summer season was studied during a 42 days experiment. One hundred twenty, day old broiler chicks were randomly allotted to 6 groups. Shatavari powder and vitamin E was added to the basal diet @ 0 and 0, 1 and 0, 1.5 and 0, 0 and 200, 1 and 200, 1.5% and 200 mg/ kg feed in treatments T1, T2, T3, T4, T5, and T6, respectively. Feed consumption was similar in all the groups. Body weight gain was higher (P